From imposed to the co-developed governance processes in IT captive offshoring engagements - Abulokwe, Nneka Nancy Lorraine (Cranfield University, 2013)
This thesis examines the impact of governance process development on engagements between onshore and offshore subsidiaries of multinational IT services organisations. Offshoring is a significant global phenomenon. Over the last decade, there has been substantial growth in the number of organisations setting up ‘captive’ (wholly owned subsidiaries) centres in offshore locations. The desired benefits of greater coordination, leveraging and sharing of knowledge have, in many instances, failed to materialise for these IT services organisations. These failures arise from a variety of causes including a lack of intra-organisational processes to coordinate and manage work, weak alignment between the parent organisation’s strategic objectives and those of the subsidiary, and the inability to navigate cross-organisational and cultural barriers. This thesis comprises three interrelated projects. The first established that organisations develop offshore subsidiaries in order to obtain one or more of a number of complex and interrelated set of strategic objectives. The second project, through the use of grounded theory, demonstrates that within one IT services organisation, imposed governance processes do not facilitate communication and engagement between the onshore and offshore subsidiaries. Cross-cultural and organisational differences inhibited the engagement between the subsidiaries, thus contributing to the failure to achieve the desired benefits of offshoring. Organisations engaged in captive offshoring are faced with two apparently contradictory sets of issues: a set of highly desirable and interrelated strategic benefits and a variety of operational challenges that arise from the imposed nature of the governance processes. The third project, a case study of a similar IT services organisation, examines how these apparently contradictory issues were resolved. The results show that it is the co-development and implementation of governance processes based on the informal working practices of both the onshore and offshore teams that enable the operational challenges established in the second project to be resolved and thus provide reconciliation between these and the achievement of the strategic benefits that drive offshoring. This thesis concludes that co-developed and implemented governance processes are a key factor in the mitigation of the deleterious effects of cross-organizational and cultural working and adds the notion of co-development and implementation of governance processes to the academic literature on the governance of outsourcing.
Keywords: Captive offshoring; Outsourcing governance; Grounded theory; Information technology